Examining the interplay between green technology, co2 emissions, and life expectancy in the asean-5 countries: insights from the panel FMOLS and DOLS approaches - Mohd Shahidan Shaari; Temitayo B. Majekodunmi; Amri Sulong; Miguel Angel Esquivias; Wan Sallha Yusoff (Discover Sustainability)
Abstract Conference of Parties (COP28) emphasized the critical need to support vulnerable nations, particularly in Southeast Asia, by addressing climate change and enhancing climate finance mechanisms, which are vital for the overall well-being of their citizens. In response, we used the Fully Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), and Cross Sectional Autoregressive Distributed Lag (CS-ARDL) techniques to examine the effects of carbon dioxide (CO2) emissions, green technology, and health expenditures on life expectancy in five Southeast Asian countries (ASEAN-5) from 1995 to 2020. Although there is a considerable body of work on the factors that affect life expectancy, this study closes a major gap in the literature by concentrating on the ASEAN-5 nations, which have not received enough attention in studies on life expectancy. Specifically, incorporating factors such as green technology, CO2 emissions, and health expenditure, which were not considered in those earlier analyses. The CS-ARDL results reveal that green technology could significantly enhance life expectancy, while CO2 emissions could have a significantly negative impact on life expectancy. The heterogeneous results of the FMOLS and DOLS also show that heightened health expenditure significantly enhances life expectancy in Thailand and the Philippines, advocating for increased investments in healthcare infrastructure. Economic expansion emerges as a significant contributor to enhanced life expectancy in Thailand, the Philippines, and Singapore, emphasizing the importance of policies fostering sustainable economic development. Notably, adopting green technology correlates positively with increased life expectancy in Singapore and the Philippines, emphasizing the dual benefits of environmentally sustainable practices. Conversely, CO2 emissions exhibit a consistent negative correlation with life expectancy across all ASEAN-5 countries, underscoring the imperative for robust environmental policies to safeguard public health. Based on the results, we recommend that policymakers in the ASEAN-5 prioritize healthcare investments and adopt sustainable economic strategies, such as promoting clean energy and circular economies. In addition, targeted incentives for green technology, including tax breaks for renewable energy investments and subsidies for carbon capture research, should also be implemented to mitigate CO2 emissions while enhancing economic resilience, public health, and life expectancy across the region.